Sensitive detection and monitoring of senescence-associated secretory phenotype by SASP-RAP assay. - Liubao Gu; Masanori Kitamura (PLoS ONE, 2012)
Senescence-associated secretory phenotype (SASP) is characterized by abundant secretion of various proteins in senescent cells and implicated in tumor progression and inflammatory responses. However, the profile of secreted proteins in SASP is different from cell type to cell type, and currently, universal markers for SASP have not been reported. In the present investigation, we show that SASP-responsive alkaline phosphatase (SASP-RAP) serves as a sensitive, general and convenient marker for SASP. Etoposide-treated cells exhibited a senescent phenotype characterized by senile morphology, positive staining for senescence-associated β-galactosidase, growth arrest and induction of p53 and p21(WAF1/CIP1). In SASP-RAP-transfected cells, exposure to etoposide increased secretion of SASP-RAP time-dependently. The kinetics of secretion was closely correlated with that of activation of the p21(WAF1/CIP1) promoter and the p16(INK4a) promoter. The enhanced secretion of SASP-RAP by senescence was also observed in cells treated with other senescence inducers such as trichostatin A, doxorubicin and 4-phenylbutylic acid. The induction of SASP-RAP by senescence was similarly observed in natural replicative senescence. To confirm selectivity of the SASP-RAP response, cells were treated with senescence-related and -unrelated stimuli (IL-1β, LPS, TNF-α and TGF-β), and induction of senescence markers and activity of SASP-RAP were evaluated in parallel. Unlike etoposide, senescence-unrelated stimuli did not induce p53 and p21(WAF1/CIP1), and it was correlated with lack of induction of SASP-RAP. In contrast, senescence-unrelated stimuli up-regulated conventional indicators for SASP, e.g., MMP-3, IL-6 and TIMP, without induction of senescence. SASP-RAP thus serves as a selective, convenient and general marker for detection and monitoring of SASP during cellular senescence.